Nasib Do Re Mi - P. Ramlee, Tan Sri, 1928-1973 ([S.l.] : Merdeka Filem Studio [production company] ; Kuala Lumpur : Sathya Productions [distributor])
Saksikan kisah'Do Re Mi' seterusnya dalam'Nasib Do Re Mi'
Story and screenplay, S. Sudarmaji ; dialogue, P. Ramlee
Cast : Tan Sri P. Ramlee (Do) , A.R.Tompel (Re), Ibrahim Din (Mi)
Keywords: Comedy films; Melodrama in motion pictures; Musical films